2004
DOI: 10.1590/s0100-879x2004001100014
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for mutations or deletions in the CDKN2A/p16 and CDKN2B/p15 genes of Brazilian neuroblastoma patients

Abstract: Neuroblastoma, the most common extracranial tumor in childhood, has a wide spectrum of clinical and biological features. The loss of heterozygosity within the 9p21 region has been reported as a prognostic factor. Two tumor suppressor genes located in this region, the CDKN2B/p15 and CDKN2A/p16 (cyclin-dependent kinase inhibitors 2B and 2A, respectively) genes, play a critical role in cell cycle progression and are considered to be targets for tumor inactivation. We analyzed CDKN2B/p15 and CDKN2A/p16 gene altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Inactivation of p14 ARF by epigenetic mechanisms can interfere with the p53 pathway, as this increases MDM2 levels, which in turn inactivates p53 (38). Homozygous deletion of p14 ARF was observed in a higher proportion of cases than previous reports (20, 39-42). It is also possible that small deletions in the 9p21 locus, specifically at the exon 1β locus exist, which are being detected by duplex PCR but not other methods.…”
Section: Discussioncontrasting
confidence: 60%
“…Inactivation of p14 ARF by epigenetic mechanisms can interfere with the p53 pathway, as this increases MDM2 levels, which in turn inactivates p53 (38). Homozygous deletion of p14 ARF was observed in a higher proportion of cases than previous reports (20, 39-42). It is also possible that small deletions in the 9p21 locus, specifically at the exon 1β locus exist, which are being detected by duplex PCR but not other methods.…”
Section: Discussioncontrasting
confidence: 60%
“…They used multiplex PCR technique for homozygous deletion analysis and; single-strand conformation polymorphism and nucleotide sequencing for mutation analysis. By these methods they analyzed all exons of both genes, but no deletion was detected [17]. In previous studies hypermethylation of tumor-suppressor genes is found to be related to NB evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Michalowski et al found RASSF1A to be hypermethylated in 100% of cell lines and in 50-90% of tumor specimens. Other genes that were frequently methylated in NBs were CASP8, DcR1, DcR2, genes mainly associated with apoptosis [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research on ALK inhibitors is underway, this research has not led to the discovery of molecular-targeted drugs (12). Mutations in the CDKN2A gene in NB cell lines have led to dramatic reductions in the production of p16 INK4a protein (13,14). Another report confirmed the expression of p16 protein in neuroblastoma cell lines and cited reduction in 12 of 19 cases (63%) (15).…”
Section: Introductionmentioning
confidence: 90%